2009
DOI: 10.1021/jp810742z
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of Monolithic Nanoporous Copper by Chemical Dealloying of Al−Cu Alloys

Abstract: Monolithic nanoporous copper (NPC) ribbons can be fabricated through chemical dealloying of melt-spun Al-Cu alloys with 33-50 at % Cu under free corrosion conditions. The microstructure of these NPC ribbons was characterized using X-ray diffraction, scanning electron microscopy, energy dispersive X-ray analysis, and transmission electron microscopy. The experimental results show that the melt-spun Al-Cu alloys with 33-50 at % Cu are composed of one or a combination of Al 2 Cu and AlCu intermetallic compounds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
120
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(125 citation statements)
references
References 26 publications
5
120
0
Order By: Relevance
“…In fact, the heat treatment By further checking FESEM images at lower magnifications, we also found some 8 particles of micron-order in the corrosion products of #2 and #3. For example, Fig.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In fact, the heat treatment By further checking FESEM images at lower magnifications, we also found some 8 particles of micron-order in the corrosion products of #2 and #3. For example, Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Nevertheless, during conventional dealloying of crystalline alloy ribbons, the corrosion starts with dissolution of a less noble atom on a flat alloy surface of closely-packed orientation [3]. Further, it has been shown that in conventional dealloying the microstructure of starting alloy ribbons such as crystalline [3,4], amorphous [5,6], single phase [7,8] or multiphase [4,[7][8][9] affects the dealloying process and the resulting morphology to a certain extent. Similarly, we predict here that the microstructure of starting alloy films in OAD would also affect the OAD behavior and the resulting morphology in a certain unknown way.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining Cu atoms are unstable because of their large surface area, so they recrystallize to form a face-centered cubic (FCC) crystal structure. 19) As the dealloying proceeds, Cu atoms are gathered to reduce surface energy and are then arranged to form FCC crystal structure to reduce the internal energy. It thus results in both the increased strut size and intensity of XRD peaks as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many NPCs have been prepared from crystalline alloys. 1,38) The effects of the intermetallic phase in AlCu, 4,6,7) MnCu, 5,10) AlPd, 4,9) AlAu, 11) AgAu, 1,8) NiMn 12) binary alloys on the final nanoporous structure were investigated extensively. The final nanoporous metals have a sort of multimodal pore-to-ligament structures with various distribution of pore sizes and ligaments from one zone to another one.…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7) Amorphous TiCu ribbons have been fabricated by using a melt spinning method and used as a precursor for the formation of nanoporous Cu by dealloying. 13) The dealloying behaviours of crystalline TiCu alloys are, however, not clear yet.…”
Section: Introductionmentioning
confidence: 99%